Provas de Língua Portuguesa Aplicadas em Vestibulares: ainda se encontra gramática tradicional nessa seara? - Maria Lucia de Oliveira (2008)
This study attempts to shed light onto the debate about k-12 teaching of the Portuguese language through morphosyntax, i.e., by emphasizing traditional grammar ("GT"). Those who are pro-GT argue that it is still very much the subject of college entrance exams in Brazil. That view is disputed by a number of linguistic experts. This study analyzed a total of 44 multiple choice college entrance exams that were applied in years 2002 and 2006 by 22 universities (11 federal and 11 privately owned), all located in the State of Minas Gerais. From this group, it identified all GT based questions that both directly and indirectly tested the student´s grammatical proficiency. Only 12% of the selected questions, of both the federal and the private institutions, were GT based, in both years 2002 and 2006 - therefore, a small incidence. However, and again in both 2002 and 2006, 10 out of 11 private universities had at least one GT based question; among the federal institutions, 10 out of 11 had at least one GT based question in 2002, and 9 out of 11 in 2006 - therefore, a significant incidence. When comparing the exams of federal and private universities, GT seemed to be generally tested to similar degrees. In addition, this study analyzed 16 applicant´s manuals used in 2002 and 2006 by 8 universities, in order to determine whether these publications generally emphasized the status of GT. The study verified that, irrespectively of their form or content, these manuals did not significantly influence the entrance exams. Their language was generally technical, inaccessible to the students and even to certain teachers, as their terminology was geared only to those well versed in linguistics. The conclusion is that it is important to re-structure these manuals so not to over-emphasize GT, and to deconstruct their sphynx-like linguistic riddles. Finally, this study recommends that universities eliminate GT questions from entrance exams and, further, that universities work more closely with k-12 schools so to synchronize modern teaching theory and practices.